2018
DOI: 10.1590/0101-60830000000179
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography findings in conversion disorder: are there any differences in the etiopathogenesis of subtypes?

Abstract: Background: Optical coherence tomography is a contactless and fast neuroimaging method. Previous Studies have observed thinning of the ganglion cell layer and inner plexiform layer in many neurodegenerative diseases. Objective: The aim of this study was to compare the layers of ganglion cell complex in conversion disorder. Methods: This study involved 50 conversion disorder patients and 50 healthy volunteers as the control. The parameters were measured and recorded automatically by a spectral optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Previous studies have found that RNFL damage can be detected by ophthalmologic examination only after 50% of the ganglion cells were damaged. This shows that the sensitivity of RNFL is low and may explain the absence of any difference between the patient subgroups 41,42 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have found that RNFL damage can be detected by ophthalmologic examination only after 50% of the ganglion cells were damaged. This shows that the sensitivity of RNFL is low and may explain the absence of any difference between the patient subgroups 41,42 .…”
Section: Discussionmentioning
confidence: 84%
“…The choroid is one of the tissues with the most vascularization in the human body and is affected by any systemic event affecting the blood flow 41 . Recent studies suggest that the underlying pathogenesis mechanisms of neurodegenerative diseases and mental disorders may be related to neuronal inflammation 42 .…”
Section: Discussionmentioning
confidence: 99%
“… Intensity: the 'ganglion cell Layer' becomes thinner until disappearing in the fovea. Therefore, the macula appears as the darkest region [6] compared to other components of the retina with degradation in intensity until reaching the fovea, as shown in the fundus image of Figure 2(A) and the OCT in Figure 3 [7].  Lack of vessels inside: the macula is an area devoid of retinal vessels [8].…”
Section: Morphological Characteristics Of the Maculamentioning
confidence: 99%
“…Fonksiyonel Nörolojik Semptom Bozukluğunda Bilişsel Davranışçı Tedavi GİRİŞ Fonksiyonel nörolojik semptom bozukluğu (FNSD), eski adıyla konversiyon bozukluğu, nörolojik yada başka tıbbi bir hastalıkla açıklanamayan sinir sistemi belirtilerini ifade eder (1). Bununla birlikte belirtiler gerçektir ve ciddi işlevsellik kaybına neden olurlar.…”
Section: öRümunclassified